1967
DOI: 10.1111/j.1365-2621.1967.tb01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mechanical factors affecting dough development *

Abstract: Doughs of wheat flour, salt and water have been mixed at various rates and to various levels of mechanical work input. .Rheological tests have confirmed that there exists a definite level of work input which gives maximum dough development for any one flour; the results suggest, moreover, the existence of an optimum rate of work input for producing the most stable dough and the best bread.Baking tests have been used to relate the rheological parameters of the doughs with their baking performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1968
1968
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Since mechanically severed SS bonds probably revert to SH by hydrogen abstraction, the eventual effect is to weaken the dough. This is in accordance with the observations of Heaps et al 32 who found a maximum and minimum, respectively, in the graphs of viscous stress work and extensibility against rate of work input.…”
Section: Improver Actionsupporting
confidence: 81%
“…Since mechanically severed SS bonds probably revert to SH by hydrogen abstraction, the eventual effect is to weaken the dough. This is in accordance with the observations of Heaps et al 32 who found a maximum and minimum, respectively, in the graphs of viscous stress work and extensibility against rate of work input.…”
Section: Improver Actionsupporting
confidence: 81%
“…54,59 Wilson et al 54 suggested that 'it may be that higher work inputs are required for higher mixing speeds (shorter mixing times) due to time dependent hydration effects.' They noted that Kilborn and Tipples 29 used a slow-speed premix of the ingredients, thereby allowing time for hydration, and found that the work input required for peak dough development did not change with mixing speed, which was in contrast with the findings of Frazier et al, 61 who did not use a slow-speed premix in their work.…”
Section: Introductionmentioning
confidence: 99%